EFFECTIVE USE OF RETAIL MARKETING TOOLS (Marketing Journal, 2025)
This article explores the features of effective use of marketing methods in retail trade, their impact on consumer behavior, and their role in enhancing the competitiveness of retail enterprises. The analysis covers key retail marketing instruments, including pricing strategies, product assortment, advertising and promotion, customer service, and loyalty programs. The article also examines opportunities for improving retail processes through modern marketing strategies, such 195 as digital marketing, omnichannel trade approaches, and customer experience enhancement. The research findings provide practical recommendations for the effective implementation of marketing strategies in retail and the development of sustainable customer relationships.
Keywords: retail; marketing; competition; consumer; profit; product; demand